2006
DOI: 10.2131/jts.31.391
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Immortalized Hepatic Stellate Cell Line Established From Metallothionein-Null Mice

Abstract: -Hepatic stellate (HS) cells were isolated from the livers of metallothionein (MT)-null and control mice and used to establish IMS/MT(-) and IMS/N cell lines, respectively, using SV40 virus transformation. Cellular morphology, incorporation of vitamin A and expression of α-SMA, desmin and SV40 T-antigen were used to confirm that both cell lines were immortal HS cells. The growth rates of both cell lines were similar and there was little difference between cell line sensitivity to zinc. MT-null IMS/MT(-) cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Cell homogeneity was confirmed by direct microscopic observations, while cells were designated as fibroblastic following confirmation of mesenchymal marker vimentin expression, as well as absence of epithelial marker cytokeratin 19 expression. In addition, normal fibroblasts were characterized as pancreatic stellate cells following confirmation of uptake and storage of vitamin A, by auto-fluorescence stemming from retinyl acetate (Sigma) containing droplets [24]. The resultant (PaSCs) and pancreatic tumor-associated fibroblasts (which were confirmed to have lost the vitamin A droplets) were used for self-derived matrix characterization.…”
Section: Methodsmentioning
confidence: 99%
“…Cell homogeneity was confirmed by direct microscopic observations, while cells were designated as fibroblastic following confirmation of mesenchymal marker vimentin expression, as well as absence of epithelial marker cytokeratin 19 expression. In addition, normal fibroblasts were characterized as pancreatic stellate cells following confirmation of uptake and storage of vitamin A, by auto-fluorescence stemming from retinyl acetate (Sigma) containing droplets [24]. The resultant (PaSCs) and pancreatic tumor-associated fibroblasts (which were confirmed to have lost the vitamin A droplets) were used for self-derived matrix characterization.…”
Section: Methodsmentioning
confidence: 99%
“…Cd concentration was determined at the mass numbers of 111 m/z. of the liver were analyzed using high performance liquid chromatography-ICP-MS (HPLC/ICP-MS) (Miura et al, 2006). Liver samples which obtained from 2, 6, 12, and 24 hr after the single injection of CdCl 2 as described -lowed by ultracentrifugation at 105,000 x g for 1 hr at 4°C.…”
Section: Accumulation and Distribution Of CD In The Liver After Cdcl mentioning
confidence: 99%
“…In agreement with this former characterization and the proposed ancestry from HSC, we could confirm the expression of typical HSC markers including Fibronectin, α-smooth muscle actin (α-SMA), collagen type I, and Vimentin. Moreover, the cells were negative for SV40T that was used for immortalization of many other continuous HSC lines, such as LX-1, LX-2, HSC-T6, SV68-IS, A640-IS, IMS/MT (-), IMS/N, and Col-GFP HSC ( Figure 5 ) [ 10 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Western blot analysis showed that the cells are capable of expressing typical HSC markers such as Fibronectin, Vimentin, and α-SMA, while expectedly lacking expression of SV40T ( Figure 5 ). These biochemical features underpin that the cells are of HSC origin and lack SV40T that was used for immortalization of many other HSC lines (e.g., LX-1, LX-2, HSC-T6, SV68-IS, A640-IS, IMS/MT (-), IMS/N, and Col-GFP HSC) [ 10 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%